Hartree-Fock Multiplet Strengths for K I, Ca II, and Sc III - Weiss, A. W. (J Res Natl Bur Stand A Phys Chem, 1967)
Analytical approximations to Hartree-Fock wavefunctions have been computed for the 4s, 4p, and 3d states of K I, Ca II, and Sc III. Multiplet strengths for the 4s–4p and 4p–3d transitions in these ions are also computed. Examination of the results indicate that relaxation of the core in the field of the series electron accounts for a large portion of the core polarization effect, at least for the 3d level. Serious cancellation is found to invalidate the dipole velocity results of the 4p–3d transition in Ca II.